Pengaruh Persepsi Siswa Atas Lingkungan Sekolah Terhadap Prestasi Belajar Pendidikan Pancasila dan Kewarganegaraan Siswa di SMK Swasta Jakarta Timur - Yayan Sudrajat; Maman Paturahman; Suyekti Kinanthi Rejeki; Jhoni Lagun Siang (Peneliti.net, 2022)
This study aims to determine and describe the effect of students' perceptions on school environment on learning achievement of Pancasila education and student citizenship at the East Jakarta Private Vocational School. The method used in this research is the method survey with a correlational approach. The affordable population in this study were para Class XI students at the East Jakarta Private Vocational School are 251 people. Samples are taken from class XI Accounting as many as 121 people. Based on the next calculation, the average value of = 76.67, variance (S1) = 80.37 and standard balance (S) = 6.78. Proven hypothesis testing that tcount is greater than ttable, this means that H0 is rejected and H1 is accepted, that is, there is a significant effect of students' perceptions of the school environment on learning achievement of Pancasila education and citizenship of Private Vocational Schools in East Jakarta